It Started With a Kiss: Monitoring Organelle Interactions and Identifying Membrane Contact Site Components in Plants - Baillie, Alice L.; Falz, Anna-Lena; Müller-Schüssele, Stefanie J.; Sparkes, Imogen (Frontiers in Plant Science, 2020)
Organelle movement and interaction are dynamic processes. Interpreting the functional role and mechanistic detail of interactions at membrane contact sites requires careful quantification of parameters such as duration, frequency, proximity and surface area of contact, and identification of molecular components. We provide an overview of current methods used to quantify organelle interactions in plants and other organisms and propose novel applications of existing technologies to tackle this emerging topic in plant cell biology.